Perencanaan Temporary Modular Shelter sebagai Solusi Hunian Sementara: Systematic Literature Review - Sely Novita Sari; Fitri Nugraheni (G-Tech: Jurnal Teknologi Terapan, 2024)
Climate change and the increasing frequency of natural disasters highlight the importance of rapid and efficient temporary housing solutions, such as Temporary Modular Shelters. Planning for Temporary Modular Shelters is a complex process that requires consideration of various aspects, including functionality, location, materials, health, safety, transportation, regulations, environmental sustainability, and socio-cultural factors. This study employs the Systematic Literature Review (SLR) methodology to evaluate previous research on Temporary Modular Shelter planning, with primary data sources from Scopus, Sinta, and Garuda. Primary data was gathered from surveys, observations, and literature reviews, while secondary data was used as supplementary material. The data selection process focused on studies relevant to the 2018-2024 timeframe. The analysis identifies key factors, common methodologies, and sustainability principles in modular shelter planning. The findings emphasize that sustainability, resource efficiency, and the use of eco-friendly materials are crucial. Additionally, community involvement and the integration of technology play important roles in enhancing the effectiveness and sustainability of shelters.